2007
DOI: 10.1101/lm.365707
|View full text |Cite
|
Sign up to set email alerts
|

Reconsolidation of episodic memories: A subtle reminder triggers integration of new information

Abstract: Recent demonstrations of “reconsolidation” suggest that memories can be modified when they are reactivated. Reconsolidation has been observed in human procedural memory and in implicit memory in infants. This study asks whether episodic memory undergoes reconsolidation. College students learned a list of objects on Day 1. On Day 2, they received a reminder or not, and then learned a second list. Memory for List 1 was tested immediately on Day 2 (Experiment 2) or on Day 3 (Experiment 1). Although the reminder d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
567
6
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 494 publications
(618 citation statements)
references
References 32 publications
41
567
6
4
Order By: Relevance
“…Hupbach, Gomez, Hardt, and Nadel (2007) showed that updating effects are not observable immediately, though they are apparent after two days of learning List 2 in the reminder condition. Therefore, stress during the onset of reconsolidation may result in impaired updating.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hupbach, Gomez, Hardt, and Nadel (2007) showed that updating effects are not observable immediately, though they are apparent after two days of learning List 2 in the reminder condition. Therefore, stress during the onset of reconsolidation may result in impaired updating.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is reasonable to hypothesize that memory updating might be impaired under stress, a possibility we decided to explore. We used a well-established episodic memory updating paradigm recently described for humans (Hupbach, Gomez, Hardt, & Nadel, 2007;Hupbach, Hardt, Gomez, & Nadel, 2008;Hupbach, Gomez, & Nadel, 2009). This updating paradigm involves learning a list of objects on Day 1.…”
Section: Experiments 1: Effects Of Stress On Episodicmentioning
confidence: 99%
“…While reconsolidation of fear related memories has most often been studied in animals, human declarative memories may also become labile during reactivation (Hupbach, Gomez, Hardt, & Nadel, 2007;Walker, Brakefield, Hobson, & Stickgold, 2003). Human studies on reconsolidation and the effects of cortisol and NA on this process are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…With this break-down, we are able to investigate whether general memory change in the different groups is the result of participants incorporating new information (i.e. false alarms of pictures from Set 2) into the original memory (Hupbach et al, 2007, 2008) or whether new information only impairs the memory, but is not incorporated into the original memory (i.e. a lower percentage of hits) 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Brunet et al, 2008; Kindt, Soeter, & Vervliet, 2009; Sevenster, Beckers, & Kindt, 2012, 2013; Soeter & Kindt, 2012), while the other line showed that memories can be altered with behavioural manipulations (e.g. Forcato et al, 2007; Hupbach, Gomez, Hardt, & Nadel, 2007; James et al, 2015; Schwabe & Wolf, 2009; Schiller et al, 2010; Wichert, Wolf, & Schwabe, 2011; 2013a, 2013b; see also van den Hout & Engelhard, 2012). Using behavioural manipulations, reactivated memories can be updated or disrupted during reconsolidation via novel learning (Ågren, 2014).…”
mentioning
confidence: 99%